Reliability-based spares provisioning of power transformers - Cruz, Ismael G. (2006)
One of the objectives of a distribution utility is to provide its customers with an efficient, adequate, and reliable electric service at a reasonable cost. Vital components of an electric system must be maintained in order to deliver a reliable electric service. In case of failure of such components, a spare must be readily available to minimize service interruptions. The quantity of spare transformers must be just enough for the substations so as not to increase the costs of investments and inventory and still assure a sufficient reliability level. This thesis aims to determine the optimum number and timing of spare power transformers for a given planning period in order to maintain a reliable electric service when one or more power transformers fail and at the same time maintain a desirable inventory level. Weibull distribution was used as the aging failure models of the transformers. The load curtailment costs were computed using a probabilistic cost model. The proposed approach resulted in a no spare scheme for a system with a loading limits on transformers and feeders. With a scheme wherein the transformers and feeders are loaded to their full capacities, simulations resulted in a scheduling of spare transformers.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric transformers -- Reliability